Frequency of alcohol consumption in humans; the role of metabotropic glutamate receptors and downstream signaling pathways - Meyers, J L; Salling, M C; Almli, L M; Ratanatharathorn, A; Uddin, M; Galea, S; Wildman, D E; Aiello, A E; Bradley, B; Ressler, K; Koenen, K C (Translational psychiatry, 2015)
Rodent models implicate metabotropic glutamate receptors (mGluRs) and downstream signaling pathways in addictive behaviors through metaplasticity. One way mGluRs can influence synaptic plasticity is by regulating the local translation of AMPA receptor trafficking proteins via eukaryotic elongation factor 2 ( eEF2 ). However, genetic variation in this pathway has not been examined with human alcohol use phenotypes. Among a sample of adults living in Detroit, Michigan (Detroit Neighborhood Health Study; n =788; 83% African American), 206 genetic variants across the mGluR – eEF2 –AMPAR pathway (including GRM1, GRM5, HOMER1, HOMER2, EEF2K, MTOR, EIF4E, EEF2, CAMK2A, ARC, GRIA1 and GRIA4 ) were found to predict number of drinking days per month (corrected P -value <0.01) when considered as a set (set-based linear regression conducted in PLINK). In addition, a CpG site located in the 3′-untranslated region on the north shore of EEF2 (cg12255298) was hypermethylated in those who drank more frequently ( P <0.05). Importantly, the association between several genetic variants within the mGluR – eEF2 –AMPAR pathway and alcohol use behavior (i.e., consumption and alcohol-related problems) replicated in the Grady Trauma Project (GTP), an independent sample of adults living in Atlanta, Georgia ( n =1034; 95% African American), including individual variants in GRM1, GRM5, EEF2 , MTOR , GRIA1, GRIA4 and HOMER2 ( P <0.05). Gene-based analyses conducted in the GTP indicated that GRM1 (empirical P <0.05) and EEF2 (empirical P <0.01) withstood multiple test corrections and predicted increased alcohol consumption and related problems. In conclusion, insights from rodent studies enabled the identification of novel human alcohol candidate genes within the mGluR – eEF2 –AMPAR pathway.